2007
DOI: 10.1007/s11274-007-9480-x
|View full text |Cite
|
Sign up to set email alerts
|

Production of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) P(3HB-co-3HV) with a broad range of 3HV content at high yields by Burkholderia sacchari IPT 189

Abstract: The biosynthesis of poly(3-hydroxybutyrateco-3-hydroxyvalerate) from sucrose and propionic acid by Burkholderia sacchari IPT 189 was studied using a twostage bioreactor process. In the first stage, this bacterium was cultivated in a balanced culture medium until sucrose exhaustion. In the second stage, a solution containing sucrose and propionic acid as carbon source was fed to the bioreactor at various sucrose/propionic acid (s/p) ratios at a constant specific flow rate. Copolymers with 3HV content ranging fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1
14

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 14 publications
2
37
1
14
Order By: Relevance
“…In a recent study with B. sacchari, Mendonça et al, 2013 confirmed the ability of this strain to incorporate the 3HV, 4HB and 3HHx monomers upon the addition of specific co-substrates along with glucose namely odd-chain fatty acids, 4-hydroxybutyric acid and hexanoic acid, respectively [22]. B. sacchari IPT 189 has also been reported in literature to produce the copolymer P(3HB-co-3HV) when grown in sucrose and propionic acid [23].…”
Section: Introductionmentioning
confidence: 81%
“…In a recent study with B. sacchari, Mendonça et al, 2013 confirmed the ability of this strain to incorporate the 3HV, 4HB and 3HHx monomers upon the addition of specific co-substrates along with glucose namely odd-chain fatty acids, 4-hydroxybutyric acid and hexanoic acid, respectively [22]. B. sacchari IPT 189 has also been reported in literature to produce the copolymer P(3HB-co-3HV) when grown in sucrose and propionic acid [23].…”
Section: Introductionmentioning
confidence: 81%
“…15 Typical carbon sources for the PHA fermentations are sugars and fatty acids, most of the time in mineral salt media (minimal media). 13,16,17 Aside from refined fructose or fructose-containing sugars in minimal media, complex fructose-containing carbon sources have also been used for fermentations and are discussed below (Table 1). The reported results are typically not as good as is the case with minimal media, but medium costs are significantly lower.…”
Section: Production Of Phb From Chicory Roots -Comparison Of Three Cumentioning
confidence: 99%
“…Currently, continuous cultures, fed batch and cyclic or repeated fed batch modes are the main cultures for PHA production at high cell density. For P(3HB) production, fed batch cultivations have been widely used in order to achieve high cell density (Rocha et al, 2008;Shang et al, 2003;Wang and Lee, 1997;Yamane et al, 1996;Kulpreecha et al, 2009), which increases the productivity of the system, leading to low investment and reduced production costs.…”
Section: Introductionmentioning
confidence: 99%